PKM PEMBERDAYAAN MASYARAKAT DALAM PENYUSUNAN RENCANA PENGEMBANGAN ARTEFAK BUDAYA SEBAGAI WISATA DESA DI DESA SIANGAN, KECAMATAN GIANYAR, KABUPATEN GIANYAR - Agus Kurniawan; I Wayan Runa (Jurnal Abdi Daya, 2023)
The Traditional Siangan Adult Village can be found 31 kilometers northeast of Denpasar City. As a spiritual tourist village, this village has cultural potential to develop. Seven ancient sites, natural beauty, local art, and cultural traditions can all be used as a tourist attraction in the Siangan Adult Village. The indigenous village community has not fully appreciated the potential of cultural heritage to be used as a starting point for spiritual tourism. To support the tourist growth of Siangan Village, it is necessary to empower the public to inventory the heritage of cultural artifacts and its use as a tourist attraction. The Foundation Sentir Bali as a partner in the Community Partnership Programme (PKM) is expected to be able to cope with the following problems: (1) the entire cultural heritage that exists in the Adult Siangan Village has not been inventorized, (2) the historical background of the cultural patrimony existing in the Village Siangan, and (3) it has not yet been used as a spiritual tourist base. By carrying out the inventory of cultural reserves in Siangan Village and managing the cultural reserve as a tourist attraction, PKM is a form of empowerment of the community in the use of cultural reservoirs. Planning as a spiritual pathway. Archaeological documentation techniques and public archeological approaches are used in the implementation of cultural reserve management models. Partners together with the community will recognize the importance of the cultural reserve as the foundation of spiritual tourism, which implies the well-being of the community, as a result of this strategy.